La invenció literària de Sant Pere Pasqual - Riera i Sans, Jaume (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: The author reconstructs the story of Sant Pere Pasqual thanks to his detailed critical analysis of the religious works attributed to this non-existent Valencian saint of the XIII century, invented by fray Pedro San Cecilio in 1629.